A note on epidemic models with infective immigrants and vaccination - Eunha Shim (Mathematical Biosciences and Engineering)
The roles of immigration and vaccination on disease dynamics are explored in a simple setting that considers the possibility of conferred immunity. We focus on SIR and SIS models with a vaccinated class. Conditions for the existence of multiple endemic steady states and a fold bifurcation are discussed.